The relationship between resilience and quality of life in advanced cancer survivors: multiple mediating effects of social support and spirituality - Chen, Cancan; Sun, Xiaofei; Liu, Zhenya; Jiao, Miaorui; Wei, Wanhong; Hu, Yanli (Frontiers in Public Health, 2023)
Background: While previous studies have revealed a positive association between resilience and quality of life in advanced cancer survivors, the mechanisms of the relationship is still unclear. This study aimed to explore the relationships between resilience, perceived social support, spirituality, and quality of life and determine the multiple mediation effects of perceived social support and spirituality on the relationship between resilience and quality of life.Methods: With 286 advanced cancer survivors, a cross-sectional, correlational survey was adopted using convenience sampling. Resilience, perceived social support, spirituality, and quality of life This is a provisional file, not the final typeset article were evaluated by self-report questionnaires. The PROCESS macro for SPSS was used to test the multiple mediation model.The scores for resilience, perceived social support, spirituality and quality of life were positively correlated with one another. Resilience was found to be directly impact quality of life.Meanwhile, the relationship between resilience and quality of life was mediated by perceived social support (effect = 0.067, 95% CI [0.019, 0.120]) and by spirituality (effect = 0.221, 95% CI [0.134, 0.332]), respectively, and by these two serially (effect = 0.036, 95% CI [0.015, 0.067]).Perceived social support and spirituality played multiple mediating roles in the relationship between resilience and quality of life. Interventions aimed at increasing resilience, and then boosting perceived social support and spirituality may be beneficial for promoting quality of life of advanced cancer survivors.